Interface‐Coupled BiFeO3/BiMnO3 Superlattices with Magnetic Transition Temperature up to 410 K. Issue 5 (7th January 2016) - Choi, Eun‐Mi; Kleibeuker, Josée E.; Fix, Thomas; Xiong, Jie; Kinane, Christy J.; Arena, Darío; Langridge, Sean; Chen, Aiping; Bi, Zhenxing; Lee, Joon Hwan; Wang, Haiyan; Jia, Quanxi; et al.
Abstract : Enhanced magnetic transition temperatures are demonstrated in 50 nm thick (001)‐oriented (BiFeO3 ) m /(BiMnO3 ) m (BFO/BMO) superlattices (SL). Highly strained ultra‐short SLs showed a magnetic transition, T C2, up to ≈410 K as a result of ferrimagnetic interaction between BFO/BMO. All SL showed a new ferromagnetic transtion, T C1, of ≈150 K coming from Fe 4+ ‐Fe 4+ interaction explained by electron transfer/leakage from Fe 3+ to Mn 3+ .